1999
DOI: 10.1590/s0100-204x1999000800007
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do silicato de cálcio e da autoclavagem na supressividade e na conducividade de dois solos à Rhizoctonia solani

Abstract: Objetivou-se verificar o efeito da aplicação de silicato de cálcio e da esterilização na supressividade natural de um Latossolo Vermelho-Escuro (LEa) álico textura muito argilosa e na conducividade natural de uma Terra Roxa Estruturada eutrófica (TRe) ao fungo Rhizoctonia solani, em condições de casa de vegetação. Utilizou-se o delineamento inteiramente casualizado em esquema fatorial 2 x 3 x 2. Os fatores foram: duas classes de solo (LEa e TRe - 0-20 cm); três tratamentos (esterilização ou não por autoclavage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
(8 reference statements)
1
1
0
Order By: Relevance
“…Our findings confirmed that soil type influences not only the productive potential of crops, but also the development of Rhizoctonia root rot (Tamm et al, 2010). In a study with application of calcium silicate in two types of soils, there was a higher disease index (46.5) in the Eutrophic Structured Terra Roxa than in the rhodic acrisol (11.1), which confirmed the suppressive character of acrisol for R. solani (Rodrigues et al, 1999).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our findings confirmed that soil type influences not only the productive potential of crops, but also the development of Rhizoctonia root rot (Tamm et al, 2010). In a study with application of calcium silicate in two types of soils, there was a higher disease index (46.5) in the Eutrophic Structured Terra Roxa than in the rhodic acrisol (11.1), which confirmed the suppressive character of acrisol for R. solani (Rodrigues et al, 1999).…”
Section: Discussionsupporting
confidence: 82%
“…In a study with application of calcium silicate in two types of soils, there was a higher disease index (46.5) in the Eutrophic Structured Terra Roxa than in the rhodic acrisol (11.1), which confirmed the suppressive character of acrisol for R . solani (Rodrigues et al, 1999).…”
Section: Discussionmentioning
confidence: 99%